Labor mobility and the integration of European labor markets - Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper outlines the importance of labor mobility for the improvement in allocating and distributing economic resources. We are faced with an increasing lack of skilled workers and a growing tendency of unemployment amongst the low-skilled. A central political objective for the future will not only be education policy but also the recruitment of high-skilled workers from international and European labor markets. Additional skilled labor increases well-being and reduces inequality. However, internal European barriers to mobility are difficult to break through. An improved transparency of the European labor market, a greater command of languages and a standardization of the social security system can strengthen mobility. The key to mobility is in promoting the integration of international workers in the European migration process, which can be strengthened through circular migration. The European blue card initiative and the opening of labor markets to foreign graduates who have been trained in Europe could set a new course.
Keywords: F22; J15; J61; 330; Migration; migration effects; EU Eastern enlargement; free movement of workers; Internationale Arbeitsmobilität; Arbeitsmarkt; Marktintegration; EU-Binnenmarkt; Internationale Wanderung; Einwanderungsrecht; EU-Politik; EU-Staaten; EU-Staaten (Osteuropa)